25‐Hydroxyvitamin D concentrations in dogs with naturally acquired blastomycosis. (5th August 2018) - O'Brien, M.A.; McMichael, M.A.; Le Boedec, K.
Abstract : Background: Hypovitaminosis D is common in humans with tuberculosis, and adequate serum 25‐hydroxyvitamin D [25(OH)D] concentrations may improve response to therapy. The pathomechanism of Blastomyces dermatitidis is similar to that of Mycobacterium tuberculosis, but the 25(OH)D status of dogs with blastomycosis has not been investigated. Objectives: To determine if dogs with blastomycosis have lower 25(OH)D concentrations compared with healthy controls and to explore the prognostic value of 25(OH)D concentrations in blastomycosis. Animals: 35 control dogs (16 client‐owned, healthy dogs and 19 healthy, random‐source hound mixes) and 22 dogs with blastomycosis. Methods: Prospective study. Serum concentrations of 25(OH)D, parathyroid hormone (PTH), ionized calcium were measured, and biochemistry and hematology profiles were performed. The 25‐hydroxyvitamin D concentrations were compared between groups, and factors associated with 25(OH)D variation were investigated in dogs with blastomycosis. Dogs with blastomycosis were followed for up to 5 years after discharge and factors associated with survival were investigated. Results: Dogs with blastomycosis had significantly lower concentrations of 25(OH)D and PTH and higher concentrations of ionized calcium than did control dogs. In dogs with blastomycosis, 25(OH)D concentrations were independently associated with neutrophil count, pCO2, and with bone and skin involvement. The 25‐hydroxyvitamin D concentration was not associated with survival in dogs with blastomycosis, whereas lactate concentrations; bone, skin, and lymph node involvement; number of affected sites; and, presence of respiratory signs were associated with survival. Conclusions and Clinical Importance: Dogs with blastomycosis had lower 25(OH)D concentrations than did healthy controls. Despite no impact on survival, investigating the effect of 25(OH)D supplementation on recovery is warranted.